Synthesis of silver/montmorillonite nanocomposites using y-irradiation. - Shameli, Kamyar; Ahmad, Mansor; Wan Yunus, Wan Md. Zin; Ibrahim, Nor Azowa; Gharayebi, Yadollah; Sedaghat, Sajjad (Dove Medical Press, 2010)
Silver nanoparticles (Ag-NPs) were synthesized into the interlamellar space of montmorillonite (MMT) by using the γ-irradiation technique in the absence of any reducing agent or heat treatment. Silver nitrate and γ-irradiation were used as the silver precursor and physical reducing agent in MMT as a solid support. The MMT was suspended in the aqueous AgNO3 solution, and after the absorption of silver ions, Ag+ was reduced using the γ-irradiation technique. The properties of Ag/MMT nanocomposites and the diameters of Ag-NPs were studied as a function of γ-irradiation doses. The interlamellar space limited particle growth (d-spacing [ds] = 1.24–1.42 nm); powder X-ray diffraction and transmission electron microscopy (TEM) measurements showed the production of face-centered cubic Ag-NPs with a mean diameter of about 21.57–30.63 nm. Scanning electron microscopy images indicated that there were structure changes between the initial MMT and Ag/MMT nanocomposites under the increased doses of γ-irradiation. Furthermore, energy dispersive X-ray fluorescence spectra for the MMT and Ag/MMT nanocomposites confirmed the presence of elemental compounds in MMT and Ag-NPs. The results from ultraviolet-visible spectroscopy and TEM demonstrated that increasing the γ-irradiation dose enhanced the concentration of Ag-NPs. In addition, the particle size of the Ag-NPs gradually increased from 1 to 20 kGy. When the γ-irradiation dose increased from 20 to 40 kGy, the particle diameters decreased suddenly as a result of the induced fragmentation of Ag-NPs. Thus, Fourier transform infrared spectroscopy suggested that the interactions between Ag-NPs with the surface of MMT were weak due to the presence of van der Waals interactions. The synthesized Ag/MMT suspension was found to be stable over a long period of time (ie, more than 3 months) without any sign of precipitation.